Knowledge Delivery Mechanism for Autonomic Overlay Network Management - O'Sullivan, Declan; Lewis, David (IEEE, 2009)
The complexity of current computing networks and the required fluidity of their operation requires autonomy to be central to the design and implementation of a managed overlay network. This paper presents a system in which a Knowledge-based Network (KBN) is used as the delivery mechanism for management information. This allows multiple autonomous managers to co-exist, playing separate roles in the management of multiple parallel overlay networks using a single dynamic and flexible knowledge delivery mechanism.
IEEE International Conference on Autonomic Computing
PUBLISHED
Barcelona, Spain
Keywords: Computer Science; Digital Engagement; Telecommunications